Design and development of a compressed air machine using a compressed air energy storage system - Abdul Aziz, M.; ., Arifuzzaman; Shams, Fahmida; Rashid, Muhammad Mahbubur; Uddin, Md. Nasir (Asian Research Publishing Network (ARPN), 2015)
The world is in an ongoing energy crisis. Fossil fuel reserves are in critical condition and the environment is being bombarded with all kinds of pollution. Therefore, it is easy to see why any technology that brings solutions to these problems is considered to be a bounty. Among the solutions is compressed air driven machine technology. This solution does not require any type of fossil fuel and is driven by compressed air as a fuel source. A general four stroke petrol engine (IC engine) is converted to a two stroke air compressed machine. The power output is examined by supplying compressed air from the air compressor. This method will demonstrate the concept of a green, environmentally-friendly new engine technology for future generations. The experimental results show a promising maximum efficiency percentage of 23.60 under 4.5 bar pressure under a maximum load condition.